Complete chloroplast genome sequence of Chrysosplenium nudicaule (Saxifragaceae). Issue 10 (3rd October 2021) - Yan, Wen-Jie; Xiang, Ni-Yan; Yang, Tian-Ge; Qin, Rui; Liu, Hong; Liu, Xing
Abstract: Chrysosplenium nudicaule Bunge, Tibetan name 'Yajima, ' growing in the highlands of China is a perennial herb belonging to the genus Chrysosplenium Saxifragaceae. As a traditional Chinese medicine, it has been used to treat digestive diseases for hundreds of years. The complete chloroplast genome of Chrysosplenium nudicaule is 152, 775 bp in length and comprises two inverted repeats (IR, 25, 962 bp), a large single-copy region (LSC, 83, 533 bp), and a small single-copy region (SSC, 17, 318 bp). It harbors 112 genes, including 78 protein-coding genes, four ribosomal RNA genes, and 30 transfer RNA genes. In addition, the rpl32 gene was deleted. The GC content of the whole chloroplast genome is 37.54%. This chloroplast genome resource will be useful for study on the evolution and genetic diversity of C. nudicaule in the future.